“Off with the Old”: Mindfulness Practice Improves Backward Inhibition - Greenberg, Jonathan; Reiner, Keren; Meiran, Nachshon (Frontiers in Psychology, 2013)
Mindfulness practice has been linked to reduced depressive rumination and described as involving inhibition of information that has been relevant in the past and is no longer relevant in the present moment. Backward inhibition (BI) is considered to be one of the purest measures of task set inhibition, and impaired BI has been linked to depressive rumination. BI was contrasted with Competitor Rule Suppression (CRS), which is another phenomenon observed in task switching, yet one which involves episodic memory tagging of information that is currently conflicting rather than active inhibition. Although similar at baseline level, a randomly assigned group (n=38) who underwent an eight session mindfulness training program exhibited improved BI but not CRS compared to a waiting list group (n=38). Findings indicate that mindfulness improves the specific component of task set inhibition, which has previously been linked to reduced rumination. Implications regarding the potential role of task set inhibition in mediating between mindfulness and reduced rumination, as well as the role of mindfulness in “being in the present moment” are discussed.